The structures of COPI-coated vesicles reveal alternate coatomer conformations and interactions - Faini, Marco; Beck, Rainer; Brügger, Britta; Wieland, Felix T. (Science, 2012)
Transport between compartments of eukaryotic cells is mediated by coated vesicles. The archetypal protein coats COPI, COPII, and clathrin are conserved from yeast to human. Structural studies of COPII and clathrin coats assembled in vitro without membranes suggest that coat components assemble regular cages with the same set of interactions between components. Detailed three-dimensional structures of coated membrane vesicles have not been obtained. Here, we solved the structures of individual COPI-coated membrane vesicles by cryoelectron tomography and subtomogram averaging of in vitro reconstituted budding reactions. The coat protein complex, coatomer, was observed to adopt alternative conformations to change the number of other coatomers with which it interacts and to form vesicles with variable sizes and shapes. This represents a fundamentally different basis for vesicle coat assembly. The flexible coatomer complex makes contact with a variable number of neighbors and coats vesicles of variable size. The flexible coatomer complex makes contact with a variable number of neighbors and coats vesicles of variable size.